Proceedings of International Symposium on Sensor Networks, Systems and Security Advances in Computing and Networking with Applications - Rao, Nageswara S.V; Brooks, Richard R.; Wu, Chase Q. (Springer International Publishing : Imprint: Springer, 2018)
This book presents current trends that are dominating technology and society, including privacy, high performance computing in the cloud, networking and IoT, and bioinformatics. By providing chapters detailing accessible descriptions of the research frontiers in each of these domains, the reader is provided with a unique understanding of what is currently feasible. Readers are also given a vision of what these technologies can be expected to produce in the near future. The topics are covered comprehensively by experts in respective areas. Each section includes an overview that puts the research topics in perspective and integrates the sections into an overview of how technology is evolving. The book represents the proceedings of the International Symposium on Sensor Networks, Systems and Security, August 31 - September 2, 2017, Lakeland Florida.